Aphrodisiac Activity of Beligo (Benincasa hispida (Thunb.) Cogn.) Seeds of Ethanol Extract in Mice - Alim, Nur; Jasmiadi, Jasmiadi; Nadillah, Nadia; Indrawaty Kadir , Ira; Afirah, Nur (Fakultas Kedokteran Universitas Brawijaya, 2024)
Beligo (Benincasa hispida (Thunb.) Cogn.), is empirically used by the people of South Sulawesi-Indonesia as an aphrodisiac. Beligo seeds contain alkaloids, phenolics, flavonoids, and unsaturated fatty acids, which have the potential to act as aphrodisiacs. The primary objective of this research is to determine the aphrodisiac activity of an ethanol extract from beligo seeds in mice. The procedure entails extraction and aphrodisiac evaluation using introduction, climbing, and coitus test parameters. Aphrodisiac testing was carried out for seven days using 25 mice as experimental animals, divided into five groups. Each group consists of four males and one female. Group I was given Sod. CMC 1% as a negative control; II, III, and IV were given ethanol extracts of beligo seeds at doses of 350mg/kg, 700mg/kg, 1400mg/kg BW, and group V, as a positive control, was given Yohimbine. The results showed that the ethanol extract of beligo seeds at doses of 350mg/kg BW, 700mg/kg BW, and 1400mg/kg BW had aphrodisiac activity (p=0.0001) compared to Sod. CMC 1% based on data on the amount of introduction and climbing. However, based on data on the number of coitus, it showed that the ethanol extract of beligo seeds at doses of 350mg/kg BW (p=0.072) had no aphrodisiac activity, 700mg/kg BW (p=0.007), 1400mg/kg BW (p=0.0001) had aphrodisiac activity compared to Na-CMC 1% and only a dose of 1400 mg/kg BW had the same aphrodisiac activity compared with Yohimbine (p=0.967). It is concluded that the ethanol extract of beligo seeds had aphrodisiac activity.